PERANAN IBADAH KONTEKSTUAL BAGI PERTUMBUHAN ROHANI REMAJA DI GEREJA KRISTEN JAWA BATURETNO - THERESIA INSANI GUSTI; JUSTIN NIAGA SIMAN JUNTAK (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2023)
Every Christian in order to live the work of God's grace is generally expressed by the form of worship. In addition to the work of worship can be done with other things like praying, praising and otherwise, but the essence of this appeal is not only formality but to establish intimate relationship with the transcendent in a theological reflection. The church has a role to provide spiritual service to build and improve someone's religiusity, and every church certainly has a difference in the way in particular in theology of so that the model of worship between one church with another church has a difference with each reflection charge. One of the